If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -7)(9x + 3) = 0 Reorder the terms: (-7 + 4x)(9x + 3) = 0 Reorder the terms: (-7 + 4x)(3 + 9x) = 0 Multiply (-7 + 4x) * (3 + 9x) (-7(3 + 9x) + 4x * (3 + 9x)) = 0 ((3 * -7 + 9x * -7) + 4x * (3 + 9x)) = 0 ((-21 + -63x) + 4x * (3 + 9x)) = 0 (-21 + -63x + (3 * 4x + 9x * 4x)) = 0 (-21 + -63x + (12x + 36x2)) = 0 Combine like terms: -63x + 12x = -51x (-21 + -51x + 36x2) = 0 Solving -21 + -51x + 36x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-7 + -17x + 12x2) = 0 Factor a trinomial. 3((-1 + -3x)(7 + -4x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333Subproblem 2
Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75Solution
x = {-0.3333333333, 1.75}
| -164-9x=86+x | | -6(2r+8)=2(x-10) | | 150*x+2500=175*x+1700 | | 65=(3-l)w | | 6m-2+m^2+3=56 | | r=3(9t-4) | | 5(3x-4)-3x-2=4 | | 5p-12+2p=6+3p-11 | | n^2+7n-18=0 | | 6(3-2x)+8x=9 | | (5y+4)(y+6)=-4(5y+4) | | -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 |